Spirituality and Health: a look through different social actors (Research, Society and Development, 2022)
There have been a lot of quality of Life surveys for some time. Since the end of the 1970s, the World Health Organization has recognized spiritual well-being as an important dimension for the balance of the individual, thus, thinking about health is not only referring to biological, physical and mental data, but to a constant search for well-being, quality of life and balance in all aspects of existence. Objective: to analyze how spirituality can influence the health and emotional aspects of different social actors with different beliefs and religions. Methodology: The research is characterized as a qualitative and descriptive study, with the purpose of knowing and describing the reality of different social actors with different beliefs and religions. Results: it was possible to perceive that the sample profile is mostly men (77.8%), brown and white with 33.3% each, with complete higher education (50%), active in the labor market (66.7%), income above one minimum wage (72.2%), living in urban areas (83.3%), of the Catholic religion (44.4%), with a regular level of quality of life (56.3%). Conclusion: The narratives point to spirituality as an important personal device to face daily divergences, consequently the aspects involving health. It is suggested that new studies be launched focused on the theme with an emphasis on the field and performance of Occupational Therapy.